Uniqueness of iterative positive solutions for the singular infinite-point p-Laplacian fractional differential system via sequential technique - Guo, Limin; Liu, Lishan; Feng, Yanqing (Nonlinear Analysis: Modelling and Control, 2020)
By sequential techniques and mixed monotone operator, the uniqueness of positive solution for singular p-Laplacian fractional differential system with infinite-point boundary conditions is obtained. Green’s function is derived, and some useful properties of Green’ function are obtained. Based on these new properties, the existence of unique positive solutions is established, moreover, an iterative sequence and a convergence rate are given, which are important for practical application, and an example is given to demonstrate the validity of our main results.